Routledge handbook of the environment in Southeast Asia - Hirsch, Philip 1957- (London Routledge, 2017)
"The environment is one of the defining issues of our times, and it is closely linked to questions and dilemmas surrounding economic development. Southeast Asia is one of the world's most economically and demographically dynamic regions, and it is also one in which a host of environmental issues raise themselves. The Routledge Handbook of the Environment in Southeast Asia is a collection of 30 chapters dealing with the most significant scholarly debates in this rapidly growing field of study. Structured in four main parts, it gives a comprehensive regional overview of, and insight into, the environment in Southeast Asia. Wide-ranging and balanced, this Handbook promotes scholarly understanding of how environmental issues are dealt with from diverse theoretical perspectives. It offers a detailed empirical understanding of the myriad environmental problems and challenges faced in Southeast Asia. This is the first publication of its kind in this field; a helpful companion for a global audience and for scholars of Southeast Asian studies from a variety of disciplines".
The environment in Southeast Asia's past, present and future / Philip Hirsch -- Thematic approaches to environment -- Understanding the physical environment of Southeast Asia: a prerequisite for better environmental management / Avijit Gupta -- Environmental histories of Southeast Asia / Peter Boomgaard -- Population growth and environmental degradation in Southeast Asia / Rodolphe de Koninck and Pham Thanh Hai -- Environmentalism / Tim Forsyth -- A Southeast Asian political ecology / Peter Vandergeest and Robin Roth -- Environmental neoliberalism in Southeast Asia / Keith Barney -- Environmental law in Southeast Asia / Ben Boer -- Environmental governance and decentralization / Robert Fisher -- Transboundary environmental politics in Southeast Asia: issues, responses and challenges / Antonio P. Contreras -- Sectoral issues in natural resources and environment -- Forests and biodiversity / Frances Seymour and Peter Kanowski -- Shifting cultivation and human interaction with forests / Rob Cramb -- Water, rivers and dams / Carl Middleton -- Social and political ecology of fisheries and aquaculture in Southeast Asia / Simon R. Bush and Melissa Marschke -- Urban environmental transitions in Southeast Asia / Peter J. Marcotullio -- Peri-urbanization and environmental issues in mega-urban regions / Edsel E. Sajor -- Adaptation to climate change in Southeast Asia: developing a relational approach / Albert Salamanca and Jonathan Rigg -- Migration and the environment / Rebecca Elmhirst -- Regional and country studies in environment -- The role of ASEAN in shaping regional environmental protection / Koh Kheng-Lian and Md. Saiful Karim -- The mekong: strategic environmental assessment of mainstream hydropower development in an international river basin / Jeremy Carew-Reid -- Cambodia: territorialisation of natural resources and environmental management / Mak Sithirith -- Indonesia: a political-economic history of environment and resources / Jeff Neilson -- Laos: abundance, scarcity and the shifting role of natural resources / Yayoi Fujita Lagerqvist -- Malaysia: structure and agency of the environmental movement / Fadzilah Majid Cooke and Adnan A. Hezri -- Myanmar: evolving environmental governance under a regime in transition / Adam Simpson -- The Philippines: historical and geographical framing of ecological degradation and environmental governance / Doracie Zoleta-Nantes -- Singapore: sustaining a global city-state and the challenges of environmental governance in the twenty-first century / Carl Grundy-Warr and Victor R. Savage -- Thailand: whither gender in the environmental movement? / Pinkaew Laungaramsri -- Timor Leste: embracing resource governance through ritual in a post-conflict society / Lisa Palmer -- Vietnam: governmental and societal response to emergent environmental issues in the mekong delta / Le Anh Tuan.
Includes bibliographical references and index.
Keywords: Economic development -- Environmental aspects -- Southeast Asia; Southeast Asia -- Environmental conditions